UPAYA MENINGKATKAN KUALITAS TIDUR LANSIA DENGAN METODE PEMBERIAN MADU MURNI - Nur Isriani Najamuddin; Masyita Wahab; Bella D. Shinta; Andan Firmansyah (Viva Medika, 2022)
Elderly (elderly) will experience changes both physically, mentally, spiritually and psychosocially. Complaints about difficulty sleeping at night often occur in the elderly. This is an important matter for the elderly, so an efficient and comfortable treatment is needed from side effects. Giving honey is one form of treatment with a relaxation method which is a type of non-pharmacological treatment that aims to improve the quality of sleep in the elderly. This research aims to identify the effect of honey on sleep quality in the elderly before and after giving pure honey in Galeso Village, Wonomulyo Community Health Center, Polewali Mandar Regency. This research is a quantitative research using a pre-experimental design. The research was carried out in Galeso Village from June to July 2021. The sample in this research amounted to 17 people. The analysis was tested using univariate and bivariate analysis. Sleep quality was measured using the PSQI (Pittsburgh Sleep Quality Index) questionnaire. Based on the Wilcoxon test analysis, the results showed that there was an effect of giving pure honey on sleep quality in the elderly